2019
DOI: 10.1016/j.redox.2019.101171
|View full text |Cite
|
Sign up to set email alerts
|

The glutathione system and the related thiol network in Caenorhabditis elegans

Abstract: Advances in the field of redox biology have contributed to the understanding of the complexity of the thiol-based system in mediating signal transduction. The redox environment is the overall spatiotemporal balance of oxidation-reduction systems within the integrated compartments of the cell, tissues and whole organisms. The ratio of the reduced to disulfide glutathione redox couple (GSH:GSSG) is a key indicator of the redox environment and its associated cellular health. The reaction mechanisms of glutathione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(60 citation statements)
references
References 198 publications
(284 reference statements)
3
57
0
Order By: Relevance
“…Under normal physiological conditions most of the redox-active glutathione molecules are in the reduced form (GSH) and only a minor fraction is present as glutathione disulfide (GSSG). The GSH/GSSG couple contributes to the maintenance of the reduced intracellular milieu [ 72 ] and can be used as an indicator of the redox status in C. elegans [ 73 ]. In its reduced form, glutathione can directly reduce substrates, but it also acts indirectly through the glutaredoxin system and intervenes in detoxification and repair processes in combination with glutathione S -transferase [ 74 ].…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
See 1 more Smart Citation
“…Under normal physiological conditions most of the redox-active glutathione molecules are in the reduced form (GSH) and only a minor fraction is present as glutathione disulfide (GSSG). The GSH/GSSG couple contributes to the maintenance of the reduced intracellular milieu [ 72 ] and can be used as an indicator of the redox status in C. elegans [ 73 ]. In its reduced form, glutathione can directly reduce substrates, but it also acts indirectly through the glutaredoxin system and intervenes in detoxification and repair processes in combination with glutathione S -transferase [ 74 ].…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
“…The activation of these pathways promotes, among others, the expression of catalase ( ctl-1 ), superoxide dismutase-3 ( sod-3 ), metallothionein ( mtl-1 ), heat shock proteins ( hsp ), glutathione S -transferase ( gst-4 ), glutathione peroxidase ( gpx ), γ-glutamylcysteine synthetase ( gcs-1 ), glutathione synthetase ( gss-1 ), glutathione reductase ( gsr-1 ), NAD(P)H:quinone oxidoreductase (NQO-1), or bacterial pathogen defense genes ( lys-7, spp-1 ). All these types of mutants have been used by different authors to evaluate the antioxidant effects and molecular mechanisms of action of multiple phytochemicals, including polyphenols [ 43 , 44 , 73 , 127 , 128 , 129 ].…”
Section: Methodological Approaches For Antioxidants Evaluation In mentioning
confidence: 99%
“…Glutathione (GSH) has both antioxidant and detoxifying effects. GSH regulates thiol, antioxidant component, redox transitions in cell signaling, contributing to various illnesses (8) . Periodontitis is predominantly due to exaggerated host response to pathogenic microorganisms and their products which causes an imbalance between the reactive oxygen species and antioxidant.…”
Section: Introductionmentioning
confidence: 99%
“…GSH is known to be a redox regulator. Thiol transferase is involved in GSH homeostasis, which is important for antioxidant defense (Board & Menon, ; Ferguson & Bridge, ). DHA reductase is responsible for maintaining the balance of ascorbate, which functions in scavenging reactive oxygen species (Noshi et al, ; Sofo, Scopa, Nuzzaci, & Vitti, ).…”
Section: Discussionmentioning
confidence: 99%
“…GSTs exist widely in both prokaryotic and eukaryotic species. Mammalian GSTs containing several classes have been reported: alpha, mu, pi, omega, sigma, theta, and zeta (Ferguson & Bridge, ; Mannervik, Board, Hayes, Listowsky, & Pearson, ), whereas six designated GST classes (delta, epsilon, omega, sigma, theta, and zeta), as well as some unclassified GSTs (Yamamoto & Yamada, ; Yamamoto et al, ), have been found in Bombyx mori , a lepidopteran model insect. GSTs have been investigated on insect species owing to their function in insecticide detoxification (Casida, ; Ketterman, Saisawang, & Wongsantichon, ; Li, Schuler, & Berenbaum, ; Ranson & Hemingway, ; Sawicki, Singh, Mondal, Benes, & Zimniak, ).…”
Section: Introductionmentioning
confidence: 99%